4, 5‐Ethylene‐2, 7‐Carbazole‐Based Medium‐Bandgap Conjugated Polymers with Low‐Lying HOMO Levels Toward Efficient Polymer Solar Cells with High Open‐Circuit Voltage. Issue 11 (16th April 2014) - Sun, Jiangman; Zhu, Yongxiang; Xu, Xiaofeng; Zhang, Chen; Chen, Junwu; Chen, Hongzheng; Cao, Yong
<x xml:space="preserve">Abstract</x> Three medium‐bandgap polymers based on a 4, 5‐ethylene‐2, 7‐dithienyl carbazole as the electron‐donating unit and different 5, 6‐dialkoxy‐2, 1, 3‐benzothiadiazoles as the electron‐accepting units, are synthesized as polymer donors for photovoltaic applications. The three copolymers possess highest occupied molecular oribital (HOMO) levels around −5.47 eV and medium bandgaps of about 1.94 eV. The solar cells with polymer:[6, 6]‐phenyl C71‐butyric acid methyl ester (PC71BM) = 1:4 as the active layer, show an especially high open‐circuit voltage (Voc) of 0.95 V and attain good power conversion efficiency up to 5.91%. The hole mobilities of the active layer films, measured by space‐charge‐limited current (SCLC), are up to 3.5 × 10−4 cm2 V−1 s−1. Given the favorable medium bandgaps, low‐lying HOMO levels, and good hole mobilities, these copolymers are promising candidates for the construction of a highly efficient front cell to harvest the shorter wavelength band of the solar radiation in a tandem solar cell with high Voc. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>